R=r1+r2
simple
all you have to do is leave r2 by itself...
(r2=??)
by doing so you need to subtract r1 on both sides
R-r1=r2
and by doing so you leave r2 by itself
r2=R-r1
HOPED THIS HELPED c:
Step-by-step explanation:
(f+g)(x) means f(x) + g(x).
(f−g)(x) means f(x) − g(x).
So all you have to do is add them and subtract them.
1. (f+g)(x) = f(x) + g(x)
(f+g)(x) = (3x − 7) + (2x − 4)
(f+g)(x) = 5x − 11
2. (f−g)(x) = f(x) − g(x)
(f−g)(x) = (3x − 7) − (2x − 4)
(f−g)(x) = 3x − 7 − 2x + 4
(f−g)(x) = x − 3
3. (f+g)(x) = f(x) + g(x)
(f+g)(x) = (2x + 3) + (x² + ½ x − 7)
(f+g)(x) = x² + 2½ x − 4
4. (f−g)(x) = f(x) − g(x)
(f−g)(x) = (2x + 3) − (x² + ½ x − 7)
(f−g)(x) = 2x + 3 − x² − ½ x + 7
(f−g)(x) = -x² + 1½ x + 10
Answer:
Try using an interest calculator
Step-by-step explanation:
It's a life saver!
Answer: what's 9 + 10 = 21 :) ur stuipood that's ur answer only here for the points sorry dude.
Step-by-step explanation: